11‐Deoxycortisol may be superior to cortisol in confirming a successful adrenal vein catheterization without cosyntropin: a pilot study. (May 2017) - Nilubol, Naris; Soldin, Steven J; Patel, Dhaval; Rwenji, Muthoni; Gu, Jianghong; Masika, Likhona S; Chang, Richard; Stratakis, Constantine A; Kebebew, Electron
Aim: We aimed to compare the performance of nine adrenal steroids in confirming the correct catheter position during adrenal venous sampling (AVS) without cosyntropin in patients with primary hyperaldosteronism.Materials & methods: A successful adrenal vein catheterization without cosyntropin was defined as the ratio of steroids from adrenal to peripheral veins being >3:1. AVS samples from four patients with primary hyperaldosteronism were analyzed.Results: Compared with the mean ratio of cortisol without cosyntropin, the ratios of 11‐deoxycortisol (p = 0.008), dehydroepiandrosterone (p = 0.01) and androstenedione (p = 0.008) were significantly higher. None of the ratios (n = 8) of cortisol from adrenal to peripheral veins exceeded 3:1, while all ratios of 11‐deoxycortisol (p < 0.001) were >3.Conclusion: Cosyntropin infusion during AVS may not be necessary if 11‐deoxycortisol is used to confirm catheter position.